2017
DOI: 10.1242/dev.140111
|View full text |Cite
|
Sign up to set email alerts
|

Ethical issues in human organoid and gastruloid research

Abstract: Research involving human organoids and gastruloids involves ethical issues associated with their derivation as well as their current and future uses. These include unique issues related to the extent of maturation that can be achieved in vitro or through chimeric research, as well as fundamental ethical considerations such as those concerning the provenance of human biomaterials and the use of gene-editing technologies. Many of these issues are not specifically addressed by existing ethics oversight mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 32 publications
0
85
0
1
Order By: Relevance
“…Organoids made out of human embryonic stem cells (hESCs) as well as so-called ‘gastruloids’ (table 1) relate to the fierce ethical debates on the use of embryos for research 33. Gastruloids are cultured out of human pluripotent stem cells (either hESCs or induced pluripotent stem cells (iPSCs)) and they closely recapitulate early stages of human development in a dish, including markers of primitive streak formation 33. This raises questions about the acceptability of ‘creating life in a dish’ and the extent of maturation of gastruloids that is allowed 33 35.…”
Section: Exchange Of Organoids: Questioning the Two Dichotomiesmentioning
confidence: 99%
“…Organoids made out of human embryonic stem cells (hESCs) as well as so-called ‘gastruloids’ (table 1) relate to the fierce ethical debates on the use of embryos for research 33. Gastruloids are cultured out of human pluripotent stem cells (either hESCs or induced pluripotent stem cells (iPSCs)) and they closely recapitulate early stages of human development in a dish, including markers of primitive streak formation 33. This raises questions about the acceptability of ‘creating life in a dish’ and the extent of maturation of gastruloids that is allowed 33 35.…”
Section: Exchange Of Organoids: Questioning the Two Dichotomiesmentioning
confidence: 99%
“…The hiPSCs are suitable for many in vitro studies as indicated above with expanding use of organoids for regenerative medicine, drug screening and personalised medicine . However ethical concerns associated with the use of cultured human stem cells and organoids need to be considered . Autologous human cells are highly desirable for transplantation purposes, since use of the patient's own cells avoids the major in vivo problem of immune rejection (discussed further in Part B).…”
Section: Part A: Major Advances In Tissue Culture For Bioengineering:mentioning
confidence: 99%
“…30 However ethical concerns associated with the use of cultured human stem cells and organoids need to be considered. 31,32 Autologous human cells are highly desirable for transplantation purposes, since use of the patient's own cells avoids the major in vivo problem of immune rejection (discussed further in Part B). These are extraordinary advances that extend biomedical research towards clinical translation.…”
Section: Sources Of Human Stem Cells To Form Diverse Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the issue opens with a thought-provoking piece (Huch et al, 2017) consisting of two parts: the hope of organoid research written by Huch and Knoblich, and the hype -including what it will take to overcome it -written by Lutolf and Martinez-Arias. Indeed, organoid culture is also not without some ethical challenges, as discussed in the Spotlight article from Munsie, Hyun and Sugarman (Munsie et al, 2017). The generation of human cerebral cortex in the dish, particularly coupled with genome editing, will require ethical consideration.…”
Section: What Can Organoids Tell Us About Morphogenesis?mentioning
confidence: 99%